Line Balancing Model Analysis in Improving Production Line Efficiency Case Study: PT XYZ - Dika Restu Elyuda; Wildanul Isnaini; Halwa Annisa Khoiri (OPSI, 2023)
The production line system is an important problem for the majority of manufacturing industries in Indonesia. PT XYZ is manufacturing company focuses on general construction and mining products supplier. Friction Bolt Stabilizer is one PT XYZ’s superior products. The problem in the friction bolt stabilizer production line is unbalanced distribution of work elements. Based on these problems, in this study a solution is provided by comparing the actual production line with the results of line balancing analysis. There are two methods used, namely Ranked Positional Weight and Killbridge Western Heuristic. The result is that the Killbridge western heuristic method produces the best design with a performance level of 91% line efficiency, 9% balance delay, a total of four workstations and a smoothness index value of 401.55 seconds.